Students’ spontaneous smile in the EFL classroom - doi: 10.4025/actascilangcult.v34i2.15352 - Daniela Gomes de Araújo Nobrega (Acta Scientiarum. Language and Culture, 2012)
This article discusses the importance of the students’ spontaneous smile in the EFL classroom interaction and its implication for their oral production. The findings proved that the students’ spontaneous smile served as a fundamental interactive nonverbal sign as it not only favors a closer relation among students, but also helps them in the co-construction of oral activities in group work. Summing up, the students’ spontaneous smile appeared to be a nonverbal indicative of proximity and increasing oral interaction among them.